Benefit of Intravenous Alteplase before Thrombectomy Depends on ASPECTS. Issue 4 (15th July 2022) - Broocks, Gabriel; Heit, Jeremy J.; Kuraitis, Gabriella M.; Meyer, Lukas; van Horn, Noel; Bechstein, Matthias; Thaler, Christian; Christensen, Soren; Mlynash, Michael; Lansberg, Maarten G.; Kemmling, Andre; Schön, Gerhard; et al.
Abstract : Purpose: Baseline variables could be used to guide the administration of additional intravenous alteplase (IVT) before mechanical thrombectomy (MT). The aim of this study was to determine how baseline imaging and demographic parameters modify the effect of IVT on clinical outcomes in patients with ischemic stroke due to large vessel occlusion. Methods: Multicenter retrospective cohort study of ischemic stroke patients triaged by multimodal‐CT undergoing MT treatment after direct admission to an MT‐eligible center. Inverse‐probability weighting analysis (IPW) was used to assess the treatment effect of IVT adjusted for baseline variables. Multivariable logistic regression analysis with IPW‐weighting and interaction terms for IVT was performed to predict functional independence (mRS 0‐2 at 90‐days). Results: 720 patients were included, of which 366 (51%) received IVT. In IPW, the treatment effect of IVT on outcome (mRS 0‐2) distinctively varied according to the ASPECTS subgroup (ASPECTS 9‐10: +15%, ASPECTS 6‐8: +7%, ASPECTS <6: −11%). In multivariable logistic regression analysis, IVT was independently associated with functional independence (aOR: 1.57, 95% CI: 1.16‐2.14, p  = 0.003) and the interaction term was significant for ASPECTS and IVT revealing that IVT was only significantly associated with better outcomes in patients with higher ASPECTS. No other significant baseline variable interaction terms were identified. Interpretation: ASPECTS was the only baseline variable that showed a significant interaction with IVT for outcome prediction. Use of IVT prior to MT in patients with an ASPECTS of <6 was not associated with a treatment benefit and should be considered carefully. ANN NEUROL 2022;92:588–595